Family history of colorectal tumours and implications for the adenoma-carcinoma sequence: a case control study. Issue 6 (December 1995) - Boutron, M C; Faivre, J; Quipourt, V; Senesse, P; Michiels, C
Abstract : Family history of colorectal cancer is a risk factor for sporadic colorectal cancer, but it is not known which step of the adenoma-carcinoma pathway it influences. This case control study investigated the relation between family history of cancer and colorectal adenomas and cancers. Family history of colorectal cancer (FHCRC) was as frequent in small (< 10 mm) adenoma patients (11.7%, n = 154) as in polyp free patients (10.6%, n = 426), whereas it was more frequent in patients with large adenoma(s) (18.8%, n = 208; p < 0.01). Odds ratios for FHCRC were 1.2 (p > 0.10) for small adenomas and 2.1 (p < 0.01) for large adenomas. Family history of other (non-colorectal) cancers (FHOC) was similar in the three groups. Patients with a colorectal cancer (n = 171) had more frequently a family history of cancer, both colorectal (15.8%; p < 0.01) and other cancers (35.7%; p < 0.001) than general population controls (n = 309; FHCRC: 8.1%; FHOC: 21.7%). In a logistic model, both factors were independently related to colorectal cancers (odds ratios: 1.9 (p < 0.05) for FHCRC and 2.1 (p < 0.001) for FHOC). These data suggest that family history of colorectal cancer influences only the growth of adenomas or their malignant transformation. The finding of a further predisposition to any type of cancer needs to be confirmed.